التكتلات الإقتصادية ودورها في جذب الإستثمار الأجنبي المباشر دراسة حالة مجلس التعاون الخليجي من 2012-2020 - نوعي فاطمة; بن خلفة شمس الدين; مراد مصطفى (جامعة عمار ثليجي الاغواط, 2022)
This study aims to find out the extent to which the economic bloc of the Gulf Cooperation Council countries contributes to attracting foreign direct investment, as the Gulf Cooperation Council is one of the ingredients that makes it an attractive environment for foreign direct investment in the region. Related to economic blocs and foreign direct investment and the analytical approach to know and analyze economic performance and the extent of foreign investment flows and intra-GCC trade. The study concluded several results, including the conglomeration that contributed to attracting direct investment to the countries of the Gulf Cooperation Council and increasing flows between one country to another due to the attractive investment environment, facilities and incentives. international, by raising growth rates and increasing economic development.